Climate change mitigation as a co-benefit of regenerative ranching: insights from Australia and the United States. Issue 5 (6th October 2020) - Gosnell, Hannah; Charnley, Susan; Stanley, Paige
Abstract : 'Managed grazing' is gaining attention for its potential to contribute to climate change mitigation by reducing bare ground and promoting perennialization, thereby enhancing soil carbon sequestration (SCS). Understanding why ranchers adopt managed grazing is key to developing the right incentives. In this paper, we explore principles and practices associated with the larger enterprise of 'regenerative ranching' (RR), which includes managed grazing but infuses the practice with holistic decision-making. We argue that this broader approach is appealing due to a suite of ecological, economic and social benefits, making climate change mitigation an afterthought, or 'co-benefit'. RR is challenging, however, because it requires a deep understanding of ecological processes along with a set of skills related to monitoring and moving livestock and feeding the soil microbiome. We review the literature regarding links between RR and SCS, then present results of qualitative research focused on motivators, enablers and constraints associated with RR, drawing on interviews with 52 practitioners in New South Wales, Australia and the western United States. Our analysis is guided by a conceptual model of the social–ecological system associated with RR that identifies determinants of regenerative potential. We discuss implications for rancher engagement and conclude with a consideration of leverage points for global scalability.